Speed and Expertise in Stock Picking: Older, Slower, and Wiser? - Boulland, Romain; Ornthanalai, Chayawat; Womack, Kent L. (Journal of Financial and Quantitative Analysis, 2023)
Abstract There are significant differences among sell-side analysts in how frequently they revise recommendations. We show that much of this variation is an analyst-individual trait. Analysts who change recommendations more slowly make recommendations that are more influential and generate better portfolio returns. Slower-revising analysts tend to change recommendations following corporate news that are harder to interpret by nonstock experts, and our evidence suggests that their investment value derives from their ability to better interpret hard-to-assess information. On average, analysts change recommendations less frequently as their career progresses; however, recommendation speed-style is the dominant predictor of their recommendation value.